Bulk assembly of organic metal halide nanotubes - Lin, Haoran (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
The organic metal halide hybrids welcome a new member with a one-dimensional (1D) tubular structure. Herein we report the synthesis and characterization of a single crystalline bulk assembly of organic metal halide nanotubes, (C(6)H(13)N(4))(3)Pb(2)Br(7). In a metal halide nanotube, six face-sharing metal halide dimers (Pb(2)Br(9)(5–)) connect at the corners to form rings that extend in one dimension, of which the inside and outside surfaces are coated with protonated hexamethylenetetramine (HMTA) cations (C(6)H(13)N(4)(+)). This unique 1D tubular structure possesses highly localized electronic states with strong quantum confinement, resulting in the formation of self-trapped excitons that give strongly Stokes shifted broadband yellowish-white emission with a photoluminescence quantum efficiency (PLQE) of ∼7%. Having realized single crystalline bulk assemblies of two-dimensional (2D) wells, 1D wires, and now 1D tubes using organic metal halide hybrids, our work significantly advances the research on bulk assemblies of quantum-confined materials.